Screening Key Factors in the Preparation of Alkaline-Based Adsorbents for Amoxicillin Removal Using Design of Experiments - Ismail Ya Mohammad Nazir Syah; Ngadi Norzita (E3S Web of Conferences)
Pharmaceutical contaminants, such as amoxicillin, are persistent pollutants in wastewater and resist conventional treatment methods, posing environmental challenges. This study explores glycerol pitch, a biodiesel by-product, as a sustainable precursor for synthesizing polymerized adsorbents. Sodium hydroxide (NaOH), potassium hydroxide (KOH), and lithium hydroxide (LiOH) were evaluated as catalysts for glycerol polymerization, with NaOH-based adsorbents demonstrating the highest amoxicillin removal efficiency. To identify the key factors influencing adsorption performance, a two-factorial experimental design was employed, investigating polymerization temperature, polymerization time, alkali concentration, activation temperature, and activation time. A total of 32 experimental runs confirmed calcination temperature and time as the most significant parameters affecting amoxicillin removal, achieving efficiencies of up to 14.43%. These findings validate the critical parameters for adsorbent preparation, forming the basis for subsequent optimization using response surface methodology (RSM). The study underscores the potential of NaOH-catalyzed glycerol-derived adsorbents as cost-effective and sustainable solutions for pharmaceutical wastewater treatment, contributing to waste valorization and environmental sustainability.